Corrosion Chemistry of Electrocatalysts - Li, Fu‐Min; Huang, Lei; Zaman, Shahid; Guo, Wei; Liu, Hongfang; Guo, Xingpeng; Xia, Bao Yu (Advanced materials (Weinheim), 2022)
Electrocatalysts are the core components of many sustainable energy conversion technologies that are considered the most potential solution to the worldwide energy and environmental crises. The reliability of structure and composition pledges that electrocatalysts can achieve predictable and stable performance. However, during the electrochemical reaction, electrocatalysts are influenced directly by the applied potential, the electrolyte, and the adsorption/desorption of reactive species, triggering structural and compositional corrosion, which directly affects the catalytic behaviors of electrocatalysts (performance degradation or enhancement) and invalidates the established structure–activity relationship. Therefore, it is necessary to elucidate the corrosion behavior and mechanism of electrocatalysts to formulate targeted corrosion‐resistant strategies or use corrosion reconstruction synthesis techniques to guide the preparation of efficient and stable electrocatalysts. Herein, the most recent developments in electrocatalyst corrosion chemistry are outlined, including corrosion mechanisms, mitigation strategies, and corrosion syntheses/reconstructions based on typical materials and important electrocatalytic reactions. Finally, potential opportunities and challenges are also proposed to foresee the possible development in this field. It is believed that this contribution will raise more awareness regarding nanomaterial corrosion chemistry in energy technologies and beyond. Corrosion chemistry of electrocatalysts is reviewed, which may inspire more profound research in functional nanomaterials and energy technologies.